Ubaydulloh ibn Mas’ud Sadrush-Sharia Buxoriy merosining o‘rganilish darajasi “Imagology of the East: shaping the Central Asian identity in Western and Eastern perceptions” - Tukhtayeva , Farida (The Lingua Spectrum, 2025)
This article explores the concept of Imagology in relation to the Eastern identity, with a specific focus on Central Asia (Uzbekistan, Kazakhstan, Turkmenistan, Tajikistan, Kyrgyzstan). Imagology, the study of how images of cultures and nations are constructed and represented in literature, art, and media, plays a crucial role in shaping the perception of the East in both Western and Eastern contexts. The paper examines how Central Asia has been portrayed historically and in contemporary times, both in Western literature and media, as well as in the self-representations of Central Asian nations. Through a comparative analysis of Western and Eastern perceptions, the article also investigates how Central Asian countries navigate their identity in a globalized world. Ultimately, the study sheds light on the complex interplay of external and internal narratives, contributing to the formation of the modern Central Asian identity.